Traditional Textile Data Archiving Methods in The Museum: Inventory and Collection Study Program - Fariz Al Hazmi; Harmilyanti Sulistyani; Aprina Murwanti (Record and Library Journal, 2026)
Background of the study: Textile Museum data archiving methods play a crucial role in transforming artifact collections into data. These methods aim to transform memory into knowledge and preserve physical artifacts that are vulnerable to damage. Purpose: This study aims to analyze the archiving methods of textile collections and articulate the utility value of archives at the Textile Museum. Method: This study uses a qualitative approach with a case study design at the Jakarta Textile Museum. This study examines two pillars of archival activities at the Textile Museum: (1) inventory as formal textile data, and (2) collection study program as a process of exploring textile knowledge. Findings: Archival methods, through the integration of inventory and research, yield knowledge of textiles, including their physical materials, motifs, functions, and history. Archives play a crucial role in preserving original artifacts, ensuring they are not continually physically touched. Curators serve as the primary agents, using participatory mechanisms to organize exhibitions and seminars before publishing the results in print and digital formats. Conclusion: This study contributes by offering an empirically integrated model of the information cycle of textile collections that has ensured the intellectual preservation of traditional textile heritage in a sustainable and dynamic manner